2009
DOI: 10.1111/j.1474-919x.2009.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Attraction of petrels to artificial lights in the Canary Islands: effects of the moon phase and age class

Abstract: The extent and intensity of artificial night lighting has increased with urban development worldwide. The resulting light pollution is responsible for mortality among many Procellariiformes species which show nocturnal activity on their breeding grounds. Here, we report light‐induced mortality of Procellariiformes during a 9‐year study (1998–2006) on Tenerife, the largest island of the Canary archipelago. A total of 9880 birds from nine species were found grounded, the majority being Cory’s Shearwaters Calonec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
100
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(117 citation statements)
references
References 26 publications
9
100
0
2
Order By: Relevance
“…Fallout caused by attraction to artificial light is thought to be a contributing factor to the decline of several procellariid and hydrobatid species (Ainley et al 2001, Le Corre et al 2002, Rodriguez & Rodriguez 2009, Fontaine et al 2011, Rodriguez et al 2012b, and our findings further underscore the severity of the threat that anthropogenic light poses to these birds. Annual public participation in the rescue of fledglings downed by lights has resulted in thousands of birds reaching the ocean that would otherwise not have arrived there, and reduction in light use through awareness campaigns has undoubtedly prevented many instances of light-induced mortality (e.g.…”
Section: Susceptibility To Light Attraction and Future Researchsupporting
confidence: 58%
See 4 more Smart Citations
“…Fallout caused by attraction to artificial light is thought to be a contributing factor to the decline of several procellariid and hydrobatid species (Ainley et al 2001, Le Corre et al 2002, Rodriguez & Rodriguez 2009, Fontaine et al 2011, Rodriguez et al 2012b, and our findings further underscore the severity of the threat that anthropogenic light poses to these birds. Annual public participation in the rescue of fledglings downed by lights has resulted in thousands of birds reaching the ocean that would otherwise not have arrived there, and reduction in light use through awareness campaigns has undoubtedly prevented many instances of light-induced mortality (e.g.…”
Section: Susceptibility To Light Attraction and Future Researchsupporting
confidence: 58%
“…Annual public participation in the rescue of fledglings downed by lights has resulted in thousands of birds reaching the ocean that would otherwise not have arrived there, and reduction in light use through awareness campaigns has undoubtedly prevented many instances of light-induced mortality (e.g. Ainley et al 2001, Le Corre et al 2002, Rodriguez & Rodriguez 2009, Fontaine et al 2011, Rodriguez et al 2012b). Methods to reduce overall light output, including attaching shields to bright light sources (which prevents direct upward radiation; Reed et al 1985) and simply decreasing total light output (King & Gould 1967, Miles et al 2010, have been shown to reduce total fledgling fallout in local areas.…”
Section: Susceptibility To Light Attraction and Future Researchmentioning
confidence: 99%
See 3 more Smart Citations